84. A proposal of early neonatal sep classification as prognostic predictor in hypoxic ischemic encephalopathy. Issue 4 (April 2016) - Molesti, E.; Bastianelli, M.; Gabbanini, S.; Bertini, G.; Corsini, I.; Lori, S.
Abstract : Aim of this study is to evaluate the relationships between a new classification of somatosensory-evoked-potentials in cascade (SEPs-C) with simultaneous video-electroencephalogram (VEEG) obtained by 1-h integrated neurophysyiological monitoring (1 h-IMNA) and clinical assessment by Sarnat–Sarnat (SS), Cerebral arteries Resistance-Index (RI) using pulsed-Doppler and Magnetic Resonance Imaging (MRI) as early predictors of a 1-year outcome in Hypoxic-ischemic-encephalopathy (HIE). 1 h-IMNA of VEEG and SEPs (bilateral median nerve stimulation) were assessed in 8 (4M-4F) asphyxiated term-infants within 1 and 4 weeks from birth. In all infants SS, RI and MRI were early performed. 1 h-IMNA and RI were also assessed in 20 healthy term-infants, as control-group. Trend of SEPs-C was evaluated in relation to behavioural-states during the VEEG-recording (wakefulness, quiet/active sleep). In control-group SEPs-C were present and modulated. In the 8 asphyxiated infants were identified 4 cortical SEPs' patterns: bilateral absence/pathological-alteration (A–A), monolateral absence/pathological alteration (A–N), hypovoltated/non-modulated (h/nm), normal (NN) in agreement with RI and MRI. The recognize of SEPs-C pattern during 1 h-IMNA, considering hypovoltage and/or modulation in relation to behavioural-state, especially if concording with RI and MRI's patterns, could implement the early prognostic-value to identify the moderate asphyxiated newborns. This proposal of neonatal SEPs'classification and its relations with IR and RMI call for further studies as early predictors of HIE, especially if mild.